Program Ta’limiyah: Instrumen Penguatan Nilai-Nilai Keagamaan dan Karakter Santri Baru di Lembaga Pendidikan Pesantren - Zahroh, Aminatus (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the role of the Ta’limiyah Program as an instrument for strengthening religious values and shaping the character of new students at Pondok Pesantren Miftahul Ulum Pamekasan. The research is grounded in the importance of value-based education in nurturing students who are not only intellectually capable but also spiritually and morally strong. A qualitative approach with a case study design was employed in this study. Data collection techniques included observation, in-depth interviews with caregivers and teachers (ustadzah), and documentation of teaching activities. The findings reveal that the Ta’limiyah Program effectively enhances the Qur’an reading skills of new students through the Qur’ani Sidogiri method and the talaqqi approach. Moreover, the program successfully internalizes religious values and fosters religious character through moral habituation, role modeling, and personal interactions between students and teachers. The analysis, grounded in religious-based learning, value education, and character education theories, confirms that the holistic educational approach adopted in the program fosters a conducive learning environment for the development of virtuous character. The Ta’limiyah Program thus serves as an integral instrument in realizing Islamic education that is not only focused on the mastery of knowledge but also on nurturing individuals with strong integrity.